2018
DOI: 10.1097/md.0000000000011896
|View full text |Cite
|
Sign up to set email alerts
|

Association of elevated blood serum high-sensitivity C-reactive protein levels and body composition with chronic kidney disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Recently, Tsai et al. [ 26 ] reported that a higher BFP and higher high-sensitivity (hs) CRP level were related to renal dysfunction in a general population. In this study, we also observed that CRP was an independent risk factor for CKD in the general population, and BFP was significantly associated with the prevalence of CKD in subjects with MAFLD without DM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tsai et al. [ 26 ] reported that a higher BFP and higher high-sensitivity (hs) CRP level were related to renal dysfunction in a general population. In this study, we also observed that CRP was an independent risk factor for CKD in the general population, and BFP was significantly associated with the prevalence of CKD in subjects with MAFLD without DM.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used models are Child-Pugh score, the model for end-stage liver disease (MELD) and the model for end-stage liver disease-sodium (MELD-Na) in clinical. Although the above models were widely used in clinical, the weakness of ability was shown due to the poor detection and difficult evaluation [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Several ESLD risk prediction models have been developed using traditional statistical modeling, including the Child-Pugh score [ 9 ], model for end-stage liver disease (MELD) [ 9 , 10 ], adjusted MELD scores (eg, MELD-Na score and integrated MELD score) [ 11 - 13 ], albumin-bilirubin score [ 14 ], Chronic Liver Failure Consortium (CLIF) Acute Decompensation Score [ 15 ], CLIF Sequential Organ Failure Score [ 16 ], CLIF Consortium Acute-on-Chronic Liver Failure Score [ 17 ], and a novel score recently developed by our group [ 18 ]. Unfortunately, these prediction scores were all found to have poor discrimination between survival and death [ 19 - 22 ]. In addition, these traditional risk scores cannot differentiate patients that need acute care or palliative care.…”
Section: Introductionmentioning
confidence: 99%